KORELASI KEMAMPUAN MENYIMAK DENGAN MENULIS PUISI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UMI - Ihramsari Akidah (Khazanah Pendidikan, 2020)
ABSTRACTThe research aims to see a significant correlation between the ability to listen to poetryand the ability to write poetry for students of the Indonesian Language and LiteratureStudy Program at the Faculty of Literature at the Muslim University of Indonesia(UMI).Research is an expose facto that is correlational, which consists of variable X thatis the ability to listen to poetry as an independent variable and the Y variable the abilityto write poetry as the dependent variable. In this study the population and sample werePro students gram Stuin Indonesian Language and Literature, Faculty of Letters UMI insemester 3, as well as technique used to collect this research data is observation and test.Furthermore din this study, the data collected was analyzed using descriptive statisticsof product moment correlation. The results of this study show that calculations using theproduct moment formula reach 0.08 because to find out whether or not there issignificant correlation between listening ability and writing student poetry. So, it appearsthat the acquisition value of 0.08 (r xy arithmetic) <0.388 of (t value of the productmoment table) at a significant level of 95% with the number of students 27 people. So, itneeds to be emphasized that the high ability to listen to student poetry, less influence onhis ability to write poetry.Keywords: Correlation, Listening to Poetry, Writing Poetry